Rising trend of caesarean section in primigravida at Lady Aitchison Hospital Lahore: Phenomenological analysis of indications - Ayyaz, Mehwish; Amna Khanum; Zubda Aimen; Alia; Samia Jamil; Hifza Waqar (Journal of the Pakistan Medical Association, 2022)
Objective: To highlight the rising trend of caesarean section and strategies to reduce the caesarean section rate in an urban setting. Methods: The qualitative, phenomenological study was conducted at the Lady Aitchison Hospital, Lahore, Pakistan, from October 16 to November 30, 2020, and comprised obstetrics and gynaecology practitioners principally responsible for making decisions related to caesarean sections. Data was collected through face-to-face detailed interview with each subject. The interviews were transcribed manually and codes were formed that led to themes. Results: Of the 10 subjects interviewed, 1(10%) was the department head, 2(20%) were associate professors, 2(20%) were assistant professors and 5(50%) were senior registrars. Main indications of caesarean section in primigravida were foetal distress, failed induction, failure to progress, social demand, malpresentation, eclampsia and antepartum haemorrhage. There were 5-7 themes that fell under each of these seven codes. Conclusion: With proper implementation of uniform decision-making strategies, the rate of caesarean section in primigravida can be lowered with proper antenatal assessment, cardiotocographic monitoring, obstetric skills teaching, specialists; involvement in decision making and counselling of patients. Key Words: Caesarean section, Primigravida, Phenomenology, Analysis.